Study on spalling behaviour of railway wheel steel due to cyclic loading - Yeo, Ricky Kar Wai (2018)
The safety of the railway has always been an important area of research. Crack growth in railway wheels and rails have been studied for many years to prevent any major failure that leads to disastrous accidents like derailment of trains. There are many different types of defects that could occur in the railway wheels. One type of defect would be spalling, which is a phenomenon that occurs due to fatigue crack growth under cyclic loading. Such cracks are usually initiated at the white etching layer of the wheel, which is caused by rapid heating and cooling due to excessive braking or acceleration. In this study, the main focus would be finding out the effects of different initial crack angles at the surface of the white etching layer of the wheel under cyclic loading. This would be done using the ABAQUS Version 6.14 to perform Extended Finite Element Method (XFEM) for different test simulations. In addition, the loads would be varied to observe any change in the effects of various initial crack angles. The two key measures of the effects would be the number of cycles to reach the interface between the white etching layer and wheel bulk material region, as well as the crack propagation rate. The results of the simulations would be compared to the relevant experimental studies for validation.